Pengaruh Pemikiran Dan Penafsiran Ayat Pendidikan Oleh Buya Hamka Terhadap Perkembangan Pendidikan Islam Di Indonesia - Nuraini, Nabilah (Universitas PTIQ Jakarta, 2024)
Buya Hamka, or Haji Abdul Malik Karim Amrullah, is a revolutionary figure in Islamic education in Indonesia. His progressive thoughts blend traditional Islamic values with modern ideas, creating a new educational paradigm relevant to contemporary developments. This study examines the influence of Buya Hamka's thoughts and interpretations of educational verses in the Quran on the development of Islamic education in Indonesia. Through